On the link between Earth tides and volcanic degassing - Dinger, Florian; Bobrowski, Nicole; Platt, Ulrich; Wagner, Thomas (Solid earth, 2019)
Abstract. Long-term measurements of volcanic gas emissions conducted during the last decade suggest that under certain conditions the magnitude or chemical composition of volcanic emissions exhibits periodic variations with a period of about 2 weeks. A possible cause of such a periodicity can be attributed to the Earth tidal potential. The phenomenology of such a link has been debated for long, but no quantitative model has yet been proposed. The aim of this paper is to elucidate whether a causal link between tidal forcing and variations in volcanic degassing can be traced analytically. We model the response of a simplified magmatic system to the local tidal gravity variations and derive a periodical vertical magma displacement in the conduit with an amplitude of 0.1-1 m, depending on the geometry and physical state of the magmatic system. We find that while the tide-induced vertical magma displacement presumably has no significant direct effect on the volatile solubility, the differential magma flow across the radial conduit profile may result in a significant increase in the bubble coalescence rate at a depth of several kilometres by up to several multiples of 10 %. Because bubble coalescence facilitates separation of gas from magma and thus enhances volatile degassing, we argue that the derived tidal variation may propagate to a manifestation of varying volcanic degassing behaviour. The presented model provides a first basic framework which establishes an analytical understanding of the link between the Earth tides and volcanic degassing.
Gesehen am 02.07.2019